First report on the infection of Acanthamoeba and Entamoeba in the endangered Chinese Milu deer (Elaphurus davidianus) in China - Zhouchun Li; Hongwei Long; Hongying Liu; Yunfang Shan; Yuxin Wang; Lijie Tian; Olalekan Opeyemi Ayanniyi; Kaili Gao; Xinglong Song; Yilei Zhang; Congshan Yang; Zhenyu Zhong; et al. (One Health)
The Chinese Milu deer (Elaphurus davidianus), an endangered species endemic to China, faces ongoing challenges, including low genetic diversity, disease threats, and declining habitat quality. Acanthamoeba spp. are common free-living amoebae widely distributed in natural environments and Entamoeba relies on a host for survival and is typically transmitted through the fecal oral route, capable of infecting numerous hosts, including humans and animals. This study presents the first investigation of Acanthamoeba spp. and Entamoeba spp. infections in the endangered Chinese Milu deer in China, aiming to assess these parasites' prevalence and epidemiological characteristics. We conducted a molecular examination on the fecal samples of Chinese Milu deer populations from five national nature reserves across different regions in China, intending to determine the presence of Acanthamoeba spp. and Entamoeba spp. infections by amplifying the SSU rRNA gene. Notably, in addition to detecting Entamoeba bovis and Entamoeba sp., the T4 and T5 genotypes of Acanthamoeba were also detected, which are associated with pathogenicity in humans and other animals. These findings highlight the potential health risks for this endangered deer and provide critical insights for future conservation and management efforts. Additionally, this study provides valuable data on the distribution and epidemiology of amoebic parasites in wildlife.